A device for X‐Ray elemental mapping using annular radioisotope source. (16th May 2017) - Ahmadi, Nader; Kavaz, Esra; Ertuğrul, Mehmet; Özdemir, Yüksel
Abstract : An energy‐dispersive system is described for elemental mapping by X‐ray fluorescence spectrometry. The present study describes the design of an X‐ray fluorescence spectrometer and presents its performance in elemental mapping applications. The spectrometer is based on a new ring‐shaped collimator with a pinhole in the center of it and a ring‐shaped Am‐241 isotope mounted in the collimator as a source for excitation of X‐ray fluorescence. The photons were detected by high‐resolution Si (Li) detector coupled to a multi‐channel analyser and cooled by liquid nitrogen. In this study, we used two samples; one of them was made from pure elemental powders, and the second one was a piece of a stone and three types of maps were plotted. In the maps type one, the areas of the elements were shown with a single color. These maps only show the location of the elements in the sample. In the maps type two, the area of each element was shown with different colors because of the count (intensity) related to the area. In the third type of the maps for each element, depending on the elements' position on the sample, the counts were plotted in three dimensions. The areas with higher intensity have greater height, and areas with lower intensity have lower altitude. These two last types of maps provide information about the homogeneity or heterogeneity of the elemental distribution in the samples. The spectrometer can perform non‐destructive analyses of samples and objects in the air. Copyright © 2017 John Wiley & Sons, Ltd.